Physiologic regulation of the serum concentration of 1,25-dihydroxyvitamin D by phosphorus in normal men. - Portale, A A; Halloran, B P; Morris, R C, Jr (The Journal of Clinical Investigation, 1989)
We asked this question: in normal humans, is either a normal dietary intake or normal serum concentration of phosphorus a determinant of the serum concentration of 1,25(OH)2D? In seven normal men whose dietary phosphorus was decreased from 2,300 to 625 mg/d, each intake for 8-9 d, under strictly controlled, normal metabolic conditions, we measured serum concentrations of 1,25(OH)2D daily, and concentrations of phosphorus hourly throughout a 24-h period, before and after restriction. Decreasing dietary phosphorus induced: (a) a 58% increase in serum levels of 1,25(OH)2D; (b) a 35% decrease in serum levels of phosphorus measured in the afternoon; (c) a 12% decrease in the 24-h mean serum level of phosphorus; but, (d) no decrease in morning fasting levels of phosphorus. Serum concentrations of 1,25(OH)2D varied inversely and significantly with 24-h mean concentrations of phosphorus (r = -0.77, P less than 0.001). When these data are combined with those of our prior study in which dietary phosphorus was varied over an extreme range, the relationship between serum levels of 1,25(OH)2D and 24-h mean serum levels of phosphorus is even stronger (r = -0.90, P less than 0.001). In the aggregate, the results demonstrate that in normal men, dietary phosphorus throughout a normal range and beyond, can finely regulate the renal production and serum concentration of 1,25(OH)2D, and provide evidence that this regulation is mediated by fine modulation of the serum concentration of phosphorus.